2019
DOI: 10.1038/s41598-018-38308-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Paper Based Devices Using Correction Pens

Abstract: We present a rapid (<10 s), cost-effective, unique single-step method for fabricating paper-based devices without necessitating any expensive instrumentation, simply by deploying correction pens that are otherwise commonly used for masking typos in printed or written matters. The marked regions formed by deposits from the correction pen demonstrate ubiquitous flow resistances to typical aqueous solutions and organic solvents in the transverse direction, resulting in a preferential bulk flow along the axial dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Nie et al described a one-step plotting method using a permanent marker and a metal mask for fabricating the device within 1 min [35]. Moreover, Chakraborty et al demonstrated a single-step method for fabricating a µPAD using correction pens within 10 s [36]. As opposed to wax patterning, this method required no heating steps as the ink penetrates during the plotting.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nie et al described a one-step plotting method using a permanent marker and a metal mask for fabricating the device within 1 min [35]. Moreover, Chakraborty et al demonstrated a single-step method for fabricating a µPAD using correction pens within 10 s [36]. As opposed to wax patterning, this method required no heating steps as the ink penetrates during the plotting.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…It involves visually observing the color change during a reaction and using it for either qualitative or quantitative analysis with the help of the naked eye or a visual aid. Colorimetric detection offers the most simple and frequently used detection in the areas of protein analysis [36,161,162,163,164], drug analysis [23,165,166,167], and ion detection [40,42,139,168,169,170,171], covering all the fields from biomedical assay to environmental monitoring as well as food safety discernment (Figure 7A).…”
Section: Detection Techniques and Applicationsmentioning
confidence: 99%
“…Garcia et al presented a handheld stamping process that produced a µPAD in seconds independently of the user’s technical skills [ 114 ]. We considered the fabrication methods that involve digitally control (e.g., wax printing, inkjet printing, and digital cutter) provides high reproducibility compared to the manual control methods (e.g., handwriting) [ 18 , 33 , 34 , 36 , 37 , 53 , 54 , 73 , 115 ].…”
Section: Fabrication Of µPadsmentioning
confidence: 99%
“…Last decade has witnessed an unprecented transformation of a simple “Paper” into paper‐based analytical devices, which has revolutionized point‐of‐care diagnosis and other fields . In addition to its biodegradable, porous, and biocompatible nature, availability of facile fabrication techniques has attracted microfluidic community to leverage paper for sensing applications . Currently, amalgamation of paper‐based devices, colorimetric detection and mobile phones is considered as the holy grail for developing frugal diagnostic platforms or assays to be implemented in resource‐constrained settings .…”
Section: Introductionmentioning
confidence: 99%